Mindfulness-based relapse prevention for drug addiction in Nepal: impact and implications of an initial 2-day training of trainers - Arun Jha; Bharat Goit; Robin Jha; Prerna Jha; Prabhat Kiran Pradhan; Achyut Acharya (BJPsych International)
Drug addiction is rife in Nepal, with a high relapse rate following treatment. Apart from basic psychosocial support, there are no evidence-based aftercare services for individuals in recovery. Recently, mindfulness-based interventions have shown promising results in preventing relapse. We discuss the context, challenges and opportunities of organising a 2-day intensive face-to-face mindfulness-based training for Nepalese mental health professionals to facilitate 8-week mindfulness-based relapse prevention (MBRP). Altogether, 24 participants completed the feedback questionnaire. Most were rehabilitation staff, along with a few psychologists and psychiatrists. Feedback suggested a high degree of satisfaction and provided comments to improve the programme. It has prompted us to design online MBRP training and set up a feasibility study for an MBRP programme in Nepal. If successful, this may help a huge number of individuals in recovery.